Is the association between working from home and higher frequency of drinking and heavy episodic drinking causal? A longitudinal analysis in the Norwegian workforce - Torleif Halkjelsvik; Inger Synnøve Moan (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVES: There have been concerns that the shift to more home-based work might result in increased alcohol consumption due to reduced supervision and increased accessibility of alcohol. Empirical studies indicate associations between working from home and alcohol consumption. We go beyond cross-sectional associations by using longitudinal data and directly inquiring about alcohol consumption while working from home. METHODS: Based on demographics of the Norwegian workforce, participants were recruited from an online research panel (sample sizes N=1257–4294) before (2018–2019), during (2020–2021) and after (2022–2023) pandemic restrictions that encouraged or mandated remote work. Fixed effects regression analyses controlled for stable individual-level characteristics. RESULTS: On average, employees working from home reported 28% more drinking episodes and 26% more heavy episodic drinking (HED) compared to other employees. However, changes in the frequency of remote workdays were not notably related to the frequency of drinking [B=0.02, 95% confidence interval (CI) -0.12–0.16] or HED (B=0.05, 95% CI -0.08–0.19). Furthermore, relative to other employees, employees working from home during the pandemic restrictions in 2020 and 2021 did not increase their drinking or HED frequency from pre-pandemic levels (B= -0.28, 95% CI -0.74–0.18 and B=0.02, 95% CI -0.21–0.24, respectively). Few workers reported weekly alcohol consumption during office hours while working from home (1%). CONCLUSIONS: The cross-sectional relation between working from home and alcohol consumption found in past studies was replicated, but, using longitudinal data, we demonstrated that employee characteristics confound the relation. Our findings indicate that alcohol consumption during home-based work is unlikely to constitute a significant public health threat.